HUBUNGAN PARSIAL ASSET DAN HUTANG TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA (KAJIAN DATA TAHUN 2011-2022) - Marzalina, Marzalina; Haryani, Haryani; Danil, Mahyu (Ekonomika Journal, 2024)
Quantitative research using verification methods with a national scope during the 2011-2022 period. Analyzing economic variables, namely assets, debt and their relationship to economic growth. Based on secondary data from BPS, the relationship model between variables is expressed in the equation GDP = 9036156+ 0.000141AS, meaning that every increase in assets has an impact on increasing economic growth. Likewise, the relationship between GDP and debt, with the GDP regression model = 8213950 + 0.452594 Hu. The contribution of the Asset aspect to GDP is 19.62%, while the contribution of the Debt variable to GDP is 92.30%. In descriptive statistics, it is explained that the median value of GDP over Assets and GDP over Debts is 578,555,199 and 7,507,359 respectively.